Pre-modern Globalization and Islamic Networks under Mongol Rule: Some Preliminary Considerations on the Spreading of Sufi Knowledge in Gansu-Qinghai†. Issue 2 (2nd April 2016) - Previato, Tommaso
Abstract: Exploring the relationship between globalization and Islam has proved to be a difficult task. The importance of globalization as a force in shaping the modern world has been remarked by scholars and experts of various fields, yet enough is unexplained about the mechanisms and processes of global integration in pre-modern times. The present study is a first attempt at both filling the gaps in the theoretical literature, and casting doubts upon the inherent irreconcilability between globalization and the Islamic world. At first place, the discourse of globalization is historicized: by viewing relevant processes retrospectively, with a prequel to the "age of Mongol conquest" and nomadic expansion across Eurasia (thirteenth and fourteenth centuries); and perspectively, out of the West's experience of modernity and its normative dominance over non-western societies. The nature of Islamic networks is then examined through the prism of early global exchanges, and the eastward transfer of Sufi knowledge understood as the result of strengthening connections between networks. The role of Sufism as one of the determining forces of change is further analysed, with special attention paid to the continuities and ruptures in the development of Sufi brotherhoods and Islamization of northwestern China (Gansu-Qinghai region) through the Yuan, Ming and Qing dynasties.